Comparative Analysis of Rescue-In Vitro-Maturation (r-IVM) Outcomes in Women with Diminished Ovarian Reserve (DOR) Versus Normal Ovarian Reserve (NOR) - Mohd Faizal Ahmad; Nurul Yaqin Mohd Nor; Mohammad Mahmoud Mohammad Ramadneh; Nurul Izyani Roseli; Marjanu Hikmah Elias; Norazilah Mat Jin; Muhammad Azrai Abu; Saiful Effendi Syafruddin; Ani Amelia Zainuddin; Shah Shamsul Azhar; Nao Suzuki; Abdul Kadir Abdul Karim (MDPI, 2025)
Indexed